(untitled) (Ameghiniana, 2014)
Patagosperma lubeckense gen. et sp. nov., has been found in Betancourt, a Perrnian locality of Chubut province. The fossils are mainly compressions consisting of an inner nucellus surrounded by three integumentary layers. The nucellus is attached to the integument only at its base. The seed apex is structurally eomplex having a bifid appen dix surrounded by an outermost inte gumenrary layer. The three parted integument ineludes a parenchymatous outer layer (sarcotesta), a middle sczone (sclerotesta) and a thin innermost endotesta. Comparisons with other related seed genera from Gondwana and the Equatorial Belt, as well as with extant gyrnnosperms and angiosperrns are made. The large size of these seeds, presence of a fleshy sarcotesta and a hard sclerotesta suggest a kind of biotic dispersal. The complex apex structure also suggests a relationship with a particular reproductive strategy and a biotic dispersal